O direito de punir do estado em Thomas Hobbes - Oliveira, Fernando Antônio Sodré de (2009)
The present essay has the goal to investigate the right to punish and the punishment on the political thought of Thomas Hobbes, with the purpose to verify which is the essence of the right to punish, its legitimacy and its limits, as well as inquiring which function the punishment exerts in the State, if juridical, political, or both. For this reason, the first chapter begins with the investigation of the constituting elements of the thought of Hobbes, analyzing how the rationalism, the materialism, the nominalism, the mechanicism and the Hobbesianian naturalism influence the definition of the referring concepts to the State and in the structure of its political theory. Based on these concepts, it is verified how the disruption of Hobbesianian thought happens with the philosophical and the scholastic tradition, mainly with the Aristotelian vision of human nature. After that, the factors that lead the institution of the Civil State, especially, the state of nature and the social pact are analyzed and its characteristic elements are distinguished. The second chapter has as a target to clarify the concepts of the rights of nature, law of nature and civil law, verifying in which way these elements relate to the State and the sovereign power, as well as its importance. Therefore, it is verified the concept of Jusnaturalism and the legal positivism in Hobbes and how laws of nature consist on the rational basis for the institution of the Civil State. On the third chapter, the right to punish is examined in the Civil State, its origin, limits, purpose and if this element is part of the sovereignty. Moreover, it is examined the connection between law, crime and sin in Hobbes and which is the influence of these concepts on the political obedience and the freedom of the subjects. Finally, it is verified how the punishment will consist in a political controlling instrument on the sovereign power.